INFLUENCE OF MENTAL AND ALIMENTARY FACTORS ON THE BIRTH PROCESS OF PREGNANT WOMEN. A MODERN VERSION OF THE ANCIENT METHODS OF PREPARING FOR CHILDBIRTH AND MONITORING THE CONDITION OF BABIES (Academicia Globe: Inderscience Research, 2022)
Helping pregnant women prepare for childbirth is a key factor in saving the lives of mothers and children. This is due to the fact that the benefit of the nutritional factor (good quality of food, a rational balance of calorie content of nutritional value ...) and peace of mind contribute to a safe birth. This leads to the correct development of the child in later stages.